2012
DOI: 10.1021/jp3012377
|View full text |Cite
|
Sign up to set email alerts
|

Ionization Of Amphiphilic Acidic Block Copolymers

Abstract: The ionization behavior of an amphiphilic diblock copolymer poly(n-butyl acrylate(50%)-stat-acrylic acid(50%))(100)-block-poly(acrylic acid)(100) (P(nBA(50%)-stat-AA(50%))(100)-b-PAA(100), DH50) and of its equivalent triblock copolymer P(nBA(50%)-stat-AA(50%))(100)-b-PAA(200)-b-P(nBA(50%)-stat-AA(50%))(100) (TH50) were studied by potentiometric titration either in pure water or in 0.5 M NaCl. These polymers consist of a hydrophilic acidic block (PAA) connected to a hydrophobic block, P(nBA(50%)-stat-AA(50%))(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 55 publications
6
69
0
Order By: Relevance
“…In a macromolecular context, hydrogen bonding interactions with poly(acrylic acid) have been reported to guide layer-by-layer assembly in water 20,21 as well as mucoadhesion of hydrogels. 22 Colombani and others have shown that p K a can be significantly elevated in polymer acids, 23 similar to p K a shifts found in proteins and nucleic acids. 24,25 We hypothesized that limited or altered ionization of acidic-hydrophobic diblock polymers could result in assembly stabilization via interchain hydrogen bonding and increased chain hydrophobicity.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In a macromolecular context, hydrogen bonding interactions with poly(acrylic acid) have been reported to guide layer-by-layer assembly in water 20,21 as well as mucoadhesion of hydrogels. 22 Colombani and others have shown that p K a can be significantly elevated in polymer acids, 23 similar to p K a shifts found in proteins and nucleic acids. 24,25 We hypothesized that limited or altered ionization of acidic-hydrophobic diblock polymers could result in assembly stabilization via interchain hydrogen bonding and increased chain hydrophobicity.…”
Section: Introductionsupporting
confidence: 59%
“…Indeed, PAA domains can have p K a ’s in the range of 5–6.5, significantly shifted toward neutral by the local macromolecular environment relative to small molecule carboxylic acids. 23 Global ionization state of poly(acrylic acid) (5.6 kDa standard) and p[(AA) 48 - b -(nBA) 50 ] was interrogated using ATR-IR spectroscopy in deuterated saline water, adjusted to acidic, neutral, and basic pD at constant ionic strength (Figure 2). The PAA standard was chosen to benchmark expectations for known polyacids outside the context of diblock amphiphile assembly.…”
Section: Resultsmentioning
confidence: 99%
“…27 Moreover, for the system studied herein both monomers in both blocks can be ionized. Therefore, we explored how the microstructure of the diblock copolymers altered their ionization behavior via potentiometric titration experiments.…”
Section: Ionization Behaviormentioning
confidence: 99%
“…Subsequently these solutions were back titrated with 0.1 M NaOH to allow for the determination of the evolution of ionization degree, α, with respect to pH. 27,42 Comparing the ionization behavior of the diblock copolymers (from 1 to 4) we observe the pH range in which ionization occurs (Fig. 1).…”
Section: Ionization Behaviormentioning
confidence: 99%
“…The polymer was dissolved in pure water containing sufficient NaOH so that all acrylic acid groups were ionized [57]; i.e., the degree of ionization (α) was unity. The solutions were filtered through 0.2 μm pore size GHP Acrodisc filters.…”
Section: B Sample Preparationmentioning
confidence: 99%